"Adoções" que não deram certo: o Impacto da "devolução" no desenvolvimento da criança e do adolescente na perspectiva de profissionais - Muniz, Flávia de Moura Rocha Parente (2016)
Given the scarcity of research about "disruptions", this work aimed to investigate the perception of professionals who deal with children/adolescents who were adopted and "disrupted" about the impact that this experience may have on their development. At first, it presents the history of the adoption and "disruption" aiding the understanding of the historical support practices such as the institutionalization of children and the "disruption" of adopted children. The second chapter consists of information and reflections about adoption and, in the third, deepens the "disruption" itself. Aiming to investigate the impact of the "disruption" for children and adolescents who have experienced this, individual, semi-structured interviews, were conducted with 21 professionals working in shelters in the city of Recife. Given the lack of data on the subject, all shelters in the city (14) participated in the survey, thus making possible a rough survey of the number of cases of "disruptions", in Recife, between 2009 and 2015: 35 cases involving 24 children and adolescents. Approximately one "return" every other month for the past six years. From the thematic analysis of the speeches of the participants, we observed some common reactions in children who experienced one or more disruption : aggression, rejection of a new adoption, denial reactions to the "disruption", depressive reactions (introspection and crying episodes), learning/cognitive difficulties, self-blaming and sleep disorders. In regard of the reactions of the professionals facing the "disruption of the child, it was observed the feeling of frustration, often related to the feeling of incompetence and impotence; indignation and anger; the idea that the "disruption" was best for the child and emotional detachment from the case. The professionals also critized the adoption process, especially about the preparation of adopters and the absence of a joint effort between the team of the shelters and the judiciary staff. Considering the results, it was revealed that the "disruption" is an experience that negatively impacts the children and adolescents. This study therefore aimed to highlight aspects of the child's life that are affected by this experience, thus theoretically subsidize interventions to be made by professionals who receive them when they return to the shelter, as well as law workers and therapists that work with these children and adoptees.